2000
DOI: 10.1002/(sici)1096-8628(20000515)92:2<142::aid-ajmg12>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

X‐linkage does not account for the absence of father–son similarity in plasma uric acid concentrations

Abstract: Plasma uric acid concentration aggregates in families, and this similarity has been suggested to be due, in part, to multiple shared genes. Men have higher plasma uric acid concentrations than women and are affected with gout nine times more frequently. Rare forms of hyperuricemia and gout are due to mutations of X-linked genes (HPRT1 and PRPS1). Given these observations, we tested the hypothesis that normal variation in plasma uric acid levels would display a pattern of familial similarity consistent with X-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…24 In one study of twins, the heritability of the renal clearance of urate was ~60%, whereas the estimated heritability of FEua was ~87%. 25 Other studies have shown that serum urate levels have a substantial heritable component (~40%).…”
Section: Introductionmentioning
confidence: 99%
“…24 In one study of twins, the heritability of the renal clearance of urate was ~60%, whereas the estimated heritability of FEua was ~87%. 25 Other studies have shown that serum urate levels have a substantial heritable component (~40%).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of uric acid were found to be associated with inflammation, oxidative stress, insulin resistance, dysglycemia, endothelial dysfunction, vascular, renal and cardiac stiffness, cardiac diastolic dysfunction, renal hyperfiltration and proteinuria [1921]. Studies of twins and families have shown the inheritance for both hyperuricaemia and excretion of urate via the kidneys [22]. In one study in twins, the heritability of the renal clearance of urate was 60% to 87% [23].…”
Section: Discussionmentioning
confidence: 99%
“…Rare forms of hyperuricemia and gout are caused by mutations of X-linked genes (HPRT and PRPS). All of these data suggest that genes responsible for uric acid regulation might reside on the X chromosome [7].…”
Section: Genetics Of Hyperuricemia and Juvenile Hyperuricemiamentioning
confidence: 92%
“…In a study of 892 obese members from 196 families, Reed and Price [7] found that variations in genes on the X chromosome contributed little to the normal variation in plasma uric acid concentration. They tested the hypothesis that loci along the X chromosome would influence the plasma uric acid concentration but found no regions that cosegregated with the plasma uric acid concentrations.…”
Section: Genetics Of Hyperuricemia and Juvenile Hyperuricemiamentioning
confidence: 99%